Redescription of Andrya cuniculi (Blanchard, 1891) (Cestoda: Anoplocephalidae), a parasite of Oryctolagus cuniculus (Lagomorpha) in Spain - Tenora, Frantisek; Koubková, Bozena; Feliu, Carlos (Folia parasitologica, 2002)
Andrya cuniculi (Blanchard, 1891) (Cestoda: Anoplocephalidae) is redescribed from Oryctolagus cuniculus (L.) from Spain. Large ranges of variability in body length and width, testes number and position of the cirrus sac were observed. An external seminal vesicle covered with small glandular cells is present. The pattern of development of the uterus is similar to that of Andrya rhopalocephala (Riehm, 1881). The only reliable differential characters to distinguish A. cunliculi from A. rhopalocephala are the position of the uterus in gravid segments and the position of the testes in mature segments. The uterus of A. cuniculi occupies the median field and parts of the lateral fields but is restricted to the median field in A. rhopalocephala. Testes are distributed more symmetrically lateral to the female organs in A. cuniculi but are mostly antiporal in A. rhopalocephala.
Keywords: Španělsko; králíci; Animals; Cestode Infections; Spain; zvířata; Rabbits; cestodózy; Cestoda